Assessment of the Effect of Recruitment Maneuver on Lung Aeration Through Imaging Analysis in Invasively Ventilated Patients: A Systematic Review - Pierrakos, Charalampos; Smit, Marry R.; Hagens, Laura A.; Heijnen, Nanon F. L.; Hollmann, Markus W.; Schultz, Marcus J.; Paulus, Frederique; Bos, Lieuwe D. J. (Frontiers in Physiology, 2021)
Background Recruitment maneuvers (RMs) have heterogeneous effects on lung aeration and have adverse side effects. We aimed to identify morphological, anatomical and functional imaging characteristics that might be used to predict the of RMs on lung aeration in invasively ventilated patients. Methods We performed a systemic review. Studies including invasively ventilated patients who received a RM and in whom re-aeration was examined with chest computed tomography (CT), electrical impedance tomography (EIT), and lung ultrasound (LUS) were included. Results 20 studies were identified. Different types of RMs were applied. The amount of re-aerated lung tissue after a RM was highly variable between patients in all studies, irrespective of the used imaging technique and the type of patients (ARDS, non-ARDS). Imaging findings suggesting a non-focal morphology (i.e., radiologic findings consistent with attenuations with diffuse or patchy loss of aeration) were associated with higher likelihood of recruitment and lower chance of overdistention than a focal morphology (i.e., radiological findings suggestive of lobar or segmental loss of aeration). This was independent of the used imaging technique but only observed in patients with ARDS. In patients without ARDS, the results were inconclusive. Conclusions ARDS patients with imaging findings suggestive of non-focal morphology show most re-aeration of previously consolidated lung tissue after RMs. The role of imaging techniques in predicting the effect of RMs on re-aeration in patients without ARDS remains uncertain.